Análise da atividade in silico e in vitro da quercetina contra Trypanosoma cruzi - Santos, Allen Karlos Gomes dos (Universidade Federal Rural do Semi-Árido, 2019)
The present study aimed to analyze the in silico and in vitro activity of Quercetin against Trypanosoma cruzi, Chagas disease parasite, and specifically the focus are: to analyze in silico the mechanisms of interaction of Quercetin with T. cruzi GAPDH and Arginase enzymes; to analyze in vitro the effect of Quercetin application on T. cruzi in its epimastigote phase; to estimate the inhibitory concentration of 50% of Quercetin for T. cruzi in its epimastigote phase. The first line of research to be established was the application of the drug in vitro. Thus, with the drug Quercetin obtained, pilot activity tests against T. cruzi began. This drug is in the form of a yellowish crystalline powder and, after application on parasite culture in LIT (Liver Infusion Tryptose) medium, it was noted that quercetin is practically insoluble in water, forming a large presence of precipitate. Quercetin dilution tests were conducted using different concentrations of PEG 400. Concentrations of 1, 2, and 4% exhibited good drug solubilization and bioavailability. Thus, Quercetin IC50 values and different control group formulations containing Benznidazole can be obtained. Quercetin (IC50 = 1.627 mM) was less efficient in causing T. cruzi death than control groups, but still has the potential to be included in the portfolio of compounds to be used in the treatment of Chagas disease. In silico and docking analysis showed that Quercetin exhibits affinity for the GAPDH binding site and probably prevent binding of NAD+, a cofactor necessary for enzymatic activity; and affinity for the binding site of Mn2+ and L-arginine in Arginase, probably preventing the catalytic activity of the enzyme
Monografia
Keywords: Doença de Chagas; Ancoragem Molecular; Reposicionamento de fármaco; Chagas Disease; Molecular Docking; Drug repositioning; CIENCIAS BIOLOGICAS::BIOTECNOLOGIA